Building a collaborative learning environment with the aid of new technologies - Franco, Camilo (Improving University Science Teaching and Learning, 2023)
This pedagogical exercise focuses on the role of new technologies for aiding collaborative learning and students’ engagement. Under the general goal of well aligned courses, new technologies can be useful for aiding engagement through well designed teaching activities, being a tool for supporting different ways of student participation in the classroom. From this approach, the role of new technologies is examined for the implementation of those activities, which are specifically designed for motivating and activating a collaborative learning process in the classroom. It is proposed that, irrespective of using traditional or new technologies, inquiry, reflection and discussion are key concepts for a successful implementation of engaging teaching activities. Keywords: engagement, motivation, active learning, inquiry, reflection, discussion.